A magyar agrárágazat a rendszerváltás után - Székely, Csaba (Közép-Európai Közlemények, 2012)
After the change of the political system in 1989 the ownership of the Hungarian agriculture has radically changed and in relation to this the farming structure has also changed. In addition, such changes in production, efficiency and organization have occurred which had a significant impact on the income generation of the agricultural sector, the rural employment and the development of rural areas. As a result of the accession to the EU in 2004 the farming conditions have fundamentally changed. The accession led to economic benefits, too, but due to the mistaken decisions made in the course of the preparation and since the accession, several areas of the agricultural sector are in difficulty. The new competition means a challenge for the whole sector which has changed not only the food supply, but also other areas of the society (foreign trade, energy supply, environmental protection, rural development etc.), too. The problems of the Hungarian agricultural sector can be remedied only by the better understanding of the actual situation, considering the interests of the rural population, setting long-term targets and developing overall rural development strategy.